A novel microfluidic patterning device for neuron-glia co-culture - Shi,A; Shemesh,J; Asadnia,M; Robles,UA; Green,R; Yeoh,GH; Warkiani,ME (2015)
ï¿½ 15CBMS-0001. Many biological processes in the body are regulated by synchronized activity between two cell types. To study cell-cell interactions, it is necessary to develop easy to use co-culture systems, where different cell types can be cultured within the same confined space. Designing a complete 3D biomimetic system to study these interactions in vitro requires complex protocols and use of non-conventional materials such as hydrogels. This paper reports development of a temporarily sealed microfluidic device which utilizes a novel valve design to directly and accurately co-culture two cell lines in alternating rows, allowing them to proliferate towards each other and then observe their interaction at the boundaries of their interface.